WISATAWAN ASING DENGAN PENYAKIT INFEKSI SALURAN NAFAS YANG DIRAWAT DI RSUP SANGLAH - DENPASAR - BALI - Ngurah Ra, Ida Bagus; Sajinadiyasa, I Gede Ketut (journal of internal medicine, 2009)
Each year 1 billion passengers travel by air, and over 50 million people from industrialized countries visit the developingworld and Bali is one of their choice. Travelers may be exposed to variety of pathogens and risk, and 20 to 70 percent of peoplereport some health problems while traveling. After diarrhea, respiratory infection is the most common illness affecting travelers.The aim of the study was to now characteristic foreign patients with respiratory infections hospitalized at Sanglah GeneralHospital. We have done retrospectif study to medical record of foreign patients hospitalized at Sanglah General Hospital onJanuary 2004 Ð June 2008.We had 17 patients with 13 (76.47%) Pneumonia and 4(23.53%) COPD with acute exacerbation, 13man and 4 woman, the mean of age 55.33 years old and more patients ³ 60 years old. Country of origin of patients mostlyAustralia, US, Germany, Nederland. Patients outcome; improve 14 (82.4%) and die 3 (17.6%), mean length of stay 4.35 days.Two die patients more than 60 years old and one below than 60 years but with coronary heart disease. The conclusion of this studyis respiratory infection who hospitalized at Sanglah General Hospital are dominated by pneumonia and eldery, possibility ofinfected respiratory disease seem higher in longer flight